Eksistensi Hukum Ekonomi Syariah Dalam Hukum Perdata - Maulana Ira M. Irsyad Arifin (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2021)
The history of the positiveization of Islamic civil law was carried out by the Ottoman Government in enforcing the Islamic Civil Code which consisted of 1851 articles. On the other hand, the "positivization" of Islamic civil law is the realization of the dream of Muslims since ancient times, during the Dutch East Indies government the Civil Code (KUHPerdata) was still applied, which was a translation of the Dutch Colonial Borgelijk Wetbook (BW). For now, the positiveization of Sharia Economic Law has become a necessity for Muslims, considering the practice of sharia economics has been increasingly developed through Sharia Financial Institutions. The compilation is then used as a reference in the settlement of sharia economic cases which are increasing day by day, along with the development of the Islamic Financial Institution as well. This paper seeks to examine Sharia Economic Law, Civil Law, Sharia Economic Law Materials in Civil Law and Efforts to Positivity Sharia Economic Law in Indonesia.